Influência de patógenos periodontais na patogênese da artrite experimental - Aquino, Sabrina Garcia de [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
Embora a etiologia da artrite reumatóide (AR) não seja ainda totalmente elucidada, estudos sugerem a associação entre a AR e a doença periodontal (DP). Entretanto, os mecanismos envolvidos nessa interação ainda não são bem conhecidos. Objetivo: Assim, o objetivo deste estudo foi avaliar a interação da DP induzida por Porphyromonas gingivalis (P. gingivalis) e da artrite induzida por antígeno (AIA) em camundongos e, em seguida, investigar in vitro e in vivo a influência de P. gingivalis e Prevotella nigrescens (P. nigrescens) na severidade da artrite induzida por colágeno (CIA), com foco especial no fenótipo de células T. Métodos:Camundongos C57/Bl6 foram submetidos à AIA e/ou DP induzida por P. gingivalis. Perda óssea alveolar, histopatologia, hipernocicepção e produção de citocinas articular, bem como a porcentagem de células Th17 e T reg foram analisadas. Em seguida, o efeito de P. gingivalis e P. nigrescens na diferenciação de células T e o envolvimento dos receptores tipo Toll (TLRs) foram investigados in vitro. In vivo, camundongos com CIA receberam as inoculações orais de P. gingivalis e P. nigrescens. Histopatologia articular, expressão gênica sinovial, fenótipo de células T e a produção de anticorpos anti peptídeos citrulinados (ACPA) foram analisados. Resultados: AIA não modula a reabsorção óssea alveolar induzida por P. gingivalis enquanto camundongos com AIA expostos à P. gingivalis apresentam maior inflamação articular e perda de proteoglicanos. Além disso, o aumento da hipernocicepção e da produção articular de TNF-α e IL-17, bem como a porcentagem de células Th17 nos linfonodos drenantes articulares foram induzidos por P. gingivalis em camundongos imunizados e desafiados, enquanto o efeito sobre...

Although the etiology of rheumatoid arthritis (RA) remains unknown, several studies have suggested a pathologic link between RA and periodontal disease (PD). However, the mechanisms involved in this interaction are not well known. Objectives: The aim of this study was to evaluate the basis of Porphyromonas gingivalis (P. gingivalis) -induced PD and antigen-induced arthritis (AIA) interaction in mice, and further investigate the influence of P. gingivalis and Prevotella nigrescens (P. nigrescens) on severity of collagen-induced arthritis (CIA), with a special focus on T cell phenotype in vitro and in vivo. Methods: C57/Bl6 mice were subjected to antigen-induced arthritis (AIA) and/or P. gingivalis-induced PD. Alveolar bone loss, joint histopathology, articular hypernociception and cytokine production, as well as the percentage of Th17 and Treg cells from lymph nodes were analyzed. Thus, the effect of P. gingivalis and P. nigrescens on T cell differentiation and the involvement of Toll-like receptors (TLRs) were studied. In vivo, collagen-induced arthritis mice received oral inoculations of P. gingivalis or P. nigrescens. Joint histopathology, synovial gene expression, T cell phenotype, cytokine and anti-citrullinated peptides antibodies (ACPA) production were analyzed. Results: AIA does not modulate the alveolar bone resorption levels induced by P. gingivalis whereas AIA mice exposed to P. gingivalis presented higher articular inflammatory scores and proteoglycan loss, increased hypernociception and articular production of TNF-α and IL-17 as well as higher percentage of Th17 cells in articular draining lymph nodes, while no effect on T reg cells was verified. In vitro, P. gingivalis and P. nigrescens activated dendritic cells to produce T cell affecting proinflammatory cytokines as well as strongly induced Th17 differentiation... (Complete abstract click electronic access below)
Keywords: Doenças periodontais; Artrite reumatoide